BLOOD AND LIQUOR CYTOKINES AS DIFFERENTIAL-DIAGNOSTIC MARKERS OF ACUTE MENINGITIS IN CHILDREN - Nadraga, A.B.; Khomyn, O.Ya.; Dybas, І.V.; Dasho, M.B. (World of Medicine and Biology, 2021)
The prospective study covered 93 patients aged 1 mo - 18 y. (47 children with aseptic meningitis, 26 - with purulent meningitis, 20 with neurotoxicosis). The concentration of cytokines (IL-4, IL-1b, IL-10, TNF-α) in cerebrospinal fluid and blood was determined during the first day of hospital stay. It was found that in patients with both aseptic and purulent meningitis, the levels of TNF-α, IL-1ß, IL-10 in the cerebrospinal fluid exceeded the levels of these cytokines in the blood. In patients with aseptic meningitis, activation of the Th2 immune response with active production by tissues of the nervous system of anti-inflammatory cytokines and increased levels in the cerebrospinal fluid, and vice versa, the advantage of Th1 response, characterized by intensive synthesis of proinflammatory cytokines in children with purulent meningitis. The obtained results optimize the differential diagnosis of aseptic and purulent inflammation of the meninges, allow to develop ways of differentiated correction of immune disorders, predict the severity of the disease and increase the effectiveness of treatment of these diseases.
Keywords: meningites; children; liquor; cytokines